Occlusion of Internal Carotid Artery in Kimura's Disease - Tamaki, Tomonori (Hindawi Publishing Corporation, 2010)
We describe a unique case of Kimura's disease in which cerebral infarction was caused by occlusion of the right internal carotid artery. A 25-year-old man with Kimura's disease was admitted to our hospital because of left hemiparesis. Computed tomography and magnetic resonance imaging of the head showed infarction in the right frontal and temporal lobes. Cerebral angiography demonstrated right internal carotid artery occlusion affecting the C1 segment, with moyamoya-like collateral vessels arising from the right opthalamic artery. Kimura's disease is a chronic disease characterized by the clinical triad of slowly enlarging subcutaneous masses with lymphoid hyperplasia in the head and neck. It often occurs in young Asian men. In our patient, the pathogenesis of internal carotid artery occlusion was unknown. There have only been a few case reports in which occlusion of the internal carotid artery was associated with autoimmune disease, and no previous cases of internal carotid occlusion associated with Kimura's disease have been reported. We suspected that occlusion of this patient's internal carotid artery may be caused by the autoimmune mechanism that underlies Kimura's disease.